Les actes de waqf des manuscrits arabes chrétiens de la Bibliothèque nationale de France - Gérard Troupeau (Revue des Mondes Musulmans et de la Méditerranée)
In Arabic, the words, ”waqf”, and its synonym, ”ḥabs”, refer to the legacy of a piece of property, whether this is a moveable piece of property or a building, for the benefit of Muslim or Christian institution. The author studies around 15 documents preserved in the National Library of France (BNF) ; these manuscripts, which were bequeathed to a church or a monastery, belong to Christian Arabs who established them as waqf After having translated the entire text of these documents, highlighting various elements within them, the author emphasises their interest for the study of geography as well as ecclesiastical history thanks to the informations given in these manuscripts about the founders of different waqf-s and their beneficiaries.